EFEKTIVITAS METODE DRILL DENGAN MULTIMEDIA UNTUK MENINGKATKAN KETERAMPILAN MENULIS HURUF HIRAGANA - Desiyanti, Ari (2013)
letter is one of the important aspects in learning, especially in reading and writing skills. In Japanese letters, there are three types of letters; Hiragana, Katakana and Kanji. In basic level of learners, Hiragana letters are the first letters that are introduced to them. In fact, the learners often have difficulties in mastering it especially in writing and memorizing the letters. Therefore, a method and media are needed to solve those problems such as applying drill method with media to improve Hiragana writing skill. The purpose of this study is investigating the effectiveness of drill method with multimedia to improve Hiragana writing skills and examine students' responses based on drill method and multimedia in improving Hiragana writing skill. This study uses experimental research method. The samples of the study are students of SMA N 6 Garut in 10th grade. The numbers of the students are 80 people which are divided into two classes, control class and experimental class. The Instrument of this study uses a test consist of 40 questions and 12 questions of a questionnare. Based on the results of the data analysis, it is obtained t 6.7, t table for 1% is 2.64, within value of 79 db. Then, the t value 6.7, t table for 5% is 1.99. It means that t value > t table. This means that there is a significant influence between the learners who use the drill method and multimedia than the learners who do not use the drill method and multimedia to improve the skill of writing Hiragana letters. Key words: Effectiveness, Drill, Multimedia, Hiragana Huruf merupakan salah satu aspek penting dalam pembelajaran terutama pada keterampilan menulis dan membaca. Huruf Jepang terdiri dari 3 jenis, yaitu Hiragana, Katakana dan Kanji. Bagi pembelajar tingkat dasar, yang pertama diperkenalkan adalah huruf Hiragana. Oleh karena itu, diperlukan metode dan media yang mampu mengatasi masalah tersebut seperti penerapan metode drill dengan multimedia untuk meningkatkan keterampilan menulis Hiragana. Tujuan penelitian ini adalah untuk mengetahui efektivitas metode drill dengan multimedia untuk meningkatkan keterampilan menulis Hiragana serta mengetahui tanggapan siswa mengenai metode drill dan multimedia untuk meningkatkan keterampilan menulis Hiragana. Penelitian ini menggunakan metode penelitian eksperimen. Dengan desain penelitian pretest dan posttest. Instrumen yang digunakan pada penelitian ini berupa tes dan angket. Sampel penelitian ini adalah siswa sebanyak 80 orang yang terbagi kedalam dua kelas yaitu kelas kontrol dan kelas eksperimen. Berdasarkan hasil analisis data, diperoleh hasil t hitung 6.7, t tabel untuk 1% adalah 2.64, dengan nilai db 79. Selanjutnya nilai t hitung 6.7, t tabel untuk 5% adalah 1.99. Hal ini berarti bahwa t hitung > t tabel. Hal ini berarti terdapat pengaruh yang signifikan antara peserta didik yang mengunakan metode drill dan multimedia dengan peserta didik yang tidak mengunakan metode drill dan multimedia untuk meningkatkan keterampilan menulis huruf hiragana. Kata Kunci : Efektivitas, Drill, Multimedia, Hiragana